Evasion differential games in the space of square summable sequences - Bekhzod Aminov; Marks Ruziboev (Games, 2024)
In this article, we consider simple-motion pursuit-evasion differential games in the Hilbert space of square summable sequences. We show that when the players have the same dynamic capabilities, evasion is possible under some assumptions about the initial positions of the players.
Keywords: 330; Hilbert spaces; basis; pursuer; evader; pursuit-evasion games; evasion strategy